The Urgency of Regulating the In Dubio Pro Natura Principle within the National Environmental Law System - Atabiya, M Haikal; Wulan, Evi Retno (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article examines the alleged corruption in tugboat service operations at Pangkalbalam Port between 2020 and 2022. The issue emerged from several vessels that were not charged tugboat service fees, raising suspicions of potential state losses. The case became a legal concern because service exemptions in state-owned port enterprises must comply strictly with national maritime regulations.Purposes of the Research: The purpose of this study is to conduct a juridical analysis of whether the absence of tugboat service charges constitutes a corruption offense under Indonesian anti-corruption law. This research further seeks to clarify the legal classification of vessels subject to mandatory tug services and evaluate the regulatory compliance of port operators in determining service obligations.Methods of the Research: This study applies a normative juridical method using statutory, case, and jurisprudential approaches. Data sources include case files, maritime transport laws, Ministerial Regulations on pilotage and towage services, internal tariff policies of PT Pelindo, and relevant court decisions. These legal materials are analyzed systematically to determine whether all elements of corruption and state financial loss are fulfilled based on applicable legislation.Findings of the Research: The findings prove that the vessels exempted from tugboat service charges were legally categorized as non-mandatory tug vessels under Law Number 17/2008, Ministerial Regulation PM 57/2015, and PT Pelindo’s tariff policies. No elements of abuse of authority, illicit enrichment, or state financial loss were found; therefore, the case could not proceed to prosecution. This research offers novelty by clarifying vessel-classification mechanisms and recommending improved regulatory understanding for port operators.